Distresses Around Manholes - Usama B. Ayasrah (International Journal of Advanced Science and Technology, 2020)
In this paper, distresses along analysis section street (400m long) in Jordan for surface drainage facilities (i.e. manholes and stormwater inlets) are inventoried including their prospective shapes and geometries, collected manhole samples into specific categories to assure the samples consistency, then the relationship between the geometries of manholes and the quantity of distresses analyzed by taking each distress quantities as regards to the dimension of facilities including medium and high severity of manholes under both shapes, edges, and circles.